Сравнительный анализ лексических парадигм "взаимодействие" и "отстранение" в лирике С. Клычкова и С. Есенина - Дидоренко (Мирошниченко), Мария Павловна (Харьковский национальный педагогический университет им. Г. С. Сковороды, 2011)
В статье сопоставляется лексика поэзии С. Клычкова и С. Есенина, объединенная в парадигмы "взаимодействие" и "отстранение", рассматривается система подпарадигм внутри каждой из них, сделан вывод о степени представленности категорий "взаимодействие" и "отстранение" в художественном мире поэтов.

The article compared the lexis of poetry S. Klychkov and S. Esenin, united in the paradigm of "interaction" and "estrangement", consider a system of underparadigm within each of them, concluded about the level of representation of categories "interaction" and "estrangement" in the art world of poets.
Comparative analysis of lexical paradigm "interaction" and "estrangement" in the lyrics of S. Klychkov and S. Esenin
Keywords: языковые единицы; стихотворения; антонимические парадигмы; философия; lexis; paradigm; S. Klychkov; S. Esenin; interaction; estrangement